Certain Bipolar Neutrosophic Competition Graphs - Muhammad Akram (Journal of the Indonesian Mathematical Society, 2018)
Different competitions of the real world have been designed by the bipolar neutrosophiccompetitions graphs. In this paper, we first introduce the concept of p-competition bipo-lar neutrosophic graphs. We then define generalization of bipolar neutrosophic competitiongraphs called m-step bipolar neutrosophic competition graphs. Further, we present somerelated bipolar neutrosophic graphs, including m-step bipolar neutrosophic neighbourhoodgraphs, bipolar neutrosophic economic competition graphs and m-step bipolar neutrosophiceconomic competition graphs. Finally, we describe an application of m-step bipolar neutro-sophic competition graphs.